Essentials of online payment security and fraud prevention - Montague, David A., 1967- (Hoboken, N.J. : Wiley, 2010)
"Essential guidance for preventing fraud in the card-not-present (CNP) space This book focuses on the prevention of fraud for the card-not-present transaction. The payment process, fraud schemes, and fraud techniques will all focus on these types of transactions ahead. Reveals the top 45 fraud prevention techniques Uniquely focuses on eCommerce fraud essentials Provides the basic concepts around CNP payments and the ways fraud is perpetrated If you do business online, you know fraud is a part of doing business. Essentials of Online Payment Security and Fraud Prevention equips you to prevent fraud in the CNP space." --
Includes index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Electronic funds transfers -- Security measures; Electronic commerce -- Security measures; Electronic books